Insight Into Spinocerebellar Ataxia Type 31 (SCA31) From Drosophila Model - Ishiguro, Taro; Nagai, Yoshitaka; Ishikawa, Kinya (Frontiers in Neuroscience, 2021)
Spinocerebellar ataxia type 31 (SCA31) is a progressive neurodegenerative disease characterized by degeneration of Purkinje cells in the cerebellum. Its genetic cause is a 2.5- to 3.8-kb-long complex pentanucleotide repeat insertion containing (TGGAA)n, (TAGAA)n, (TAAAA)n, and (TAAAATAGAA)n located in an intron shared by two different genes: brain expressed associated with NEDD4-1 (BEAN1) and thymidine kinase 2 (TK2). Among these repeat sequences, (TGGAA)n repeat was the only sequence segregating with SCA31, which strongly suggests its pathogenicity. In SCA31 patient brains, the mutant BEAN1 transcript containing expanded UGGAA repeats (UGGAAexp) was found to form abnormal RNA structures called RNA foci in cerebellar Purkinje cell nuclei. In addition, the deposition of pentapeptide repeat (PPR) proteins, poly(Trp-Asn-Gly-Met-Glu), translated from UGGAAexp RNA, was detected in the cytoplasm of Purkinje cells. To uncover the pathogenesis of UGGAAexp in SCA31, we generated Drosophila models of SCA31 expressing UGGAAexp RNA. The toxicity of UGGAAexp depended on its length and expression level, which was accompanied by the accumulation of RNA foci and translation of repeat-associated PPR proteins in Drosophila, consistent with the observation in SCA31 patient brains. We also revealed that TDP-43, FUS, and hnRNPA2B1, motor neuron disease-linked RNA-binding proteins bound to UGGAAexp RNA, act as RNA chaperones to regulate the formation of RNA foci and repeat-associated translation. Further research on the role of RNA-binding proteins as RNA chaperones may also provide a novel therapeutic strategy for other microsatellite repeat expansion diseases besides SCA31.